(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The subgrade soil is the supporting part of the concrete road for transferring the different traffic loads from the road surface. The strength of this soil increases its ability to receive loads, increases the durability of the concrete road, and does not cause structural failure problems. If the soil is weak, it will decrease pavement service life and cause multiple types of failure on the road such as damage to joints, an increase in stresses and deflection, and cracking. In addition, the soil stabilization process increases the soil’s strength and its tolerance to high loads, so the laboratory results showed that the use of 4% of the asphalt emulsion led to improving the gypsum soil properties and increasing the California bearing ratio to 52%. In the process of designing rigid pavement using the AASHTO design method and depending on concrete properties and subgrade properties before and after stabilization, it was found that alterations in the CBR value within the range of 27-52% and a compressive strength of 30 MPa resulted in a reduction of 7.5% in slab thickness during the design calculations. A reduction of 7.8% in slab thickness was observed upon alteration of the CBR value from a range of 27-52% and a compressive strength of 35 MPa. A reduction of 4.5% in slab thickness was observed with a variation in compressive strength from 30-35 MPa and a CBR value of 27%. A reduction of 4.8% in slab thickness was found with a variation in compressive strength from 30-35 MPa and a CBR value of 52%. Therefore, it was found that the effect of increasing the soil strength on reducing the thickness of the concrete road is greater than the effect of changing the compressive strength of concrete.